PELATIHAN PENGGUNAAN TEKNOLOGI GLOBAL POSITIONING SYSTEM (GPS) SEBAGAI ALAT BANTU OPERASI PENANGKAPAN IKAN BAGI GENERASI MILLENNIAL ACEH - Imamshadiqin Imamshadiqin; Syahrial syahrial; Erniati erniati; 'Akla akla; Erlangga erlangga; Imanullah imanullah; Yudho andika; Muliari muliari; Arina ruzanna; Salmarika salmarika; Irmayunita irmayunita; Wilman shobara (Universitas Teuku Umar, 2022)
Training on the use of GPS technology as a fishing operation tool for Aceh's millennial generation was carried out on June 21 – 27, 2021 at the Unimal Campus Reuleut, North Aceh Regency and the Indian Ocean. This training aims to educate and improve the skills of the millennial generation of Aceh Province to take advantage of the use of GPS to help detecting the presence of fish in the ocean. The training was delivered using a community development approach that included lectures and focus group discussions (FGD), as well as theory and field practice. The training was well-structured, smooth, and successful, involving the Acehnese millennial generation aged 20-25 years, with the training divided into four stages planning, preparation, implementation, and monitoring and evaluation. The material provided in the theory class includes knowledge and developments in the use of GPS globally, whereas the practical class involves the operation of GPS directly on the ship. The monitoring and evaluation results revealed that participants benefited greatly from using GPS catching tools in detecting the presence of fish, allowing them to increase catches and easily locate fishing grounds.